PENGARUH PENERAPAN PSAK KONVERGENSI IFRS TERHADAP LAPORAN KEUANGAN - Sabil Sabil; Muhammad Qadaruddin; Amin Setio Lestiningsih (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2018)
Accurate and relevant financial reports are indispensable for users in terms of presenting accounting information. This is also based on the increasing globalization characterized by the operation of multinational companies in various countries has been instrumental in bridging the meeting of different accounting practices. From this it is the underlying IAI Convergence to IFRS in setting financial accounting standards. Data collection techniques used are documentation, interviews, observation. The method of data analysis is comparative / comparison analysis that is using statistical calculation in the form of quantitative (amount) by using SPSS as counting tool. The results showed that with the application of IFRS Convergence PSAK there is a significant difference to the treatment of fixed assets. These differences are caused by different treatment in revaluation / revaluation of fixed assets.